Fatherless Condition and Early Childhood Social Emotional Development: Kondisi Tanpa Ayah dan Perkembangan Sosial Emosional pada Masa Kanak-kanak Awal - Lailatul Ramadhina; Agus Salim (Academia Open, 2025)
General Background: Early childhood social emotional development constitutes a foundational aspect of personality formation and future adjustment within family and educational environments. Specific Background: The phenomenon of fatherless families has increasingly drawn scholarly attention due to concerns regarding children’s behavioral regulation, emotional expression, and social interaction patterns. Knowledge Gap: Despite growing discussions on parental roles, limited qualitative exploration has focused specifically on how father absence relates to social emotional characteristics in early childhood within contextual family settings. Aims: This study aims to analyze the social emotional development of early childhood experiencing fatherless conditions and to describe observable behavioral patterns in daily interactions. Results: The findings indicate variations in emotional regulation, social responsiveness, self-confidence, and peer interaction, reflecting the centrality of paternal presence in shaping children’s socio-emotional experiences. Novelty: The study provides contextualized qualitative evidence highlighting the lived experiences of children in father-absent families within early childhood education settings. Implications: These results contribute to the discourse on parental involvement and offer practical considerations for educators and families in supporting children’s socio-emotional growth in father-absent contexts. Keywords: Fatherless, Early Childhood, Social Emotional Development, Parental Involvement, Qualitative Study Key Findings Highlights: Children displayed distinct emotional regulation patterns in father-absent families. Peer interaction tendencies varied according to family structure conditions. Self-confidence and social responsiveness reflected differences in paternal presence.